Contextual differences in the moderating effects of price consciousness and social desirability in pay-what-you-want (PWYW) pricing - Rabbanee, Fazlul; Sharma, Piyush; Roy, Rajat (Elsevier, 2021)
This research explores the trade-offs that customers make between different economic, social, and psychological considerations to arrive at a pay-what-you-want (PWYW) pricing decision. Specifically, it examines the differences in the moderating effects of price consciousness and social desirability on customers’ PWYW pricing decisions between private and public contexts. Three empirical studies are used to test the hypotheses. The findings reveal that the internal reference price and fairness perception positively affect the PWYW prices. These effects are moderated negatively (attenuated) by price consciousness and positively (enhanced) by social desirability. Moreover, the moderating effect of price consciousness is stronger in the private context, while the moderating effect of social desirability is stronger in the public context. These findings offer novel insights on the cognitive process underlying the trade-off between economic and socio-psychological boundary conditions (i.e., price consciousness and social desirability) that drive contrasting effects on customer decision-making in PWYW pricing.